Study on dynamic reliability of permanent magnet gear transmission system with wear and failure correlation. (January 2022) - Jiang, Song; Li, Wei; Xin, Gaifang; Sheng, Lianchao; Wang, Yuqiao
Highlights: Considering of PMSM, gear structure and load torque, the system electromechanical coupling dynamic model is established. On this basis of the nonlinear damage theory and modified P-S-N curve, the dynamic reliability of gear single failure mode is predicted. Based on the Copula function, the reliability of the failure modes and different gears are associated. Abstract: To reveal the features of the gear wear and failure correlation on the system reliability, comprehensive consideration of PMSM characteristics, gear internal structure and load torque, the permanent magnet gear transmission system dynamic model is established based on the motor theory and Maxwell equation. The gear variable amplitude fatigue load spectrum is statistically analyzed by rain flow counting method and Goodman theory. On this basis of nonlinear damage theory and modified P-S-N curve, the dynamic reliability of gear single failure mode considering the number of random loads and strength degradation is predicted. Finally, based on the Copula function, the change regularities of the system dynamic reliability are analyzed by using the relationship between the correlation function and reliability.